Epidemiology, Diagnosis, and Management of Tibial Tubercle Avulsion Fractures in Adolescents. Issue 4 (April 2020) - Cole, Wendell W.; Brown, Symone M.; Vopat, Bryan; Heard, Wendell M.R.; Mulcahey, Mary K.
Abstract : Although rare, tibial tubercle avulsion fracture must be considered in the differential diagnosis for the pediatric patient presenting with acute knee pain. In the adolescent population, tibial tubercle avulsion fracture is a rare injury that is typically seen in boys who engage in sporting activities that involve jumping or sprinting. The proximal tibial physis closes distally in the posteromedial to anterolateral direction, creating an environment that predisposes the tubercle to a potential avulsion injury. Historically, the Ogden classification has guided nonoperative and operative management of this condition. Multiple fracture fixation methods have been described with the overall goal of restoring the extensor mechanism and the joint surface.